2022
DOI: 10.1186/s41256-022-00262-2
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate surgical tourism service organizations in China: indicators system development and a pilot application

Abstract: Background Surgical tourism is an emerging economic sector, with the most growth potential demonstrated in China's health industry before the COVID-19 pandemic. Surgical tourism accounts for a large part of medical tourism services in China, with high requirements in terms of quality and safety. By contrast, China suffers from insufficient measurement tools and theoretical research. The aim of this study was to develop a set of reliable and feasible indicators by augmenting the Donabedian model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A study has unveiled that the interaction between ApoE and ACE2 is responsible for SARS-CoV-2 infection, leading to heightened susceptibility and severity of COVID-19 in carriers of the ApoE ε4 allele. 25 In a murine model of SARS-CoV-2 infection, ApoE genotyping can predict the poor prognosis of COVID-19, with mice carrying the ApoE4 gene exhibiting significantly reduced survival rates. 26,27 This study found that higher ApoE levels in omicron patients were associated with a higher risk for mortality and a lower OS rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has unveiled that the interaction between ApoE and ACE2 is responsible for SARS-CoV-2 infection, leading to heightened susceptibility and severity of COVID-19 in carriers of the ApoE ε4 allele. 25 In a murine model of SARS-CoV-2 infection, ApoE genotyping can predict the poor prognosis of COVID-19, with mice carrying the ApoE4 gene exhibiting significantly reduced survival rates. 26,27 This study found that higher ApoE levels in omicron patients were associated with a higher risk for mortality and a lower OS rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that patients exhibiting elevated levels of ApoE displayed lower absolute counts of CD3 and CD8 lymphocytes. A study has unveiled that the interaction between ApoE and ACE2 is responsible for SARS‐CoV‐2 infection, leading to heightened susceptibility and severity of COVID‐19 in carriers of the ApoE ε4 allele 25 . In a murine model of SARS‐CoV‐2 infection, ApoE genotyping can predict the poor prognosis of COVID‐19, with mice carrying the ApoE4 gene exhibiting significantly reduced survival rates 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The initial indicator list was consisted of major domains of national Healthy China Initiative as well as specific indicators available under the context of the target region. Afterwards, 7-rounds of focus group discussions were adopted to determine which indicators should be added into or excluded from the initial indicator list [41,45]. In total 7 experts from official departments, academe and universities who were familiar with the project very well were invited to join the group discussions and review the indicators based on local realities, and suggestions were also collected from 18 practitioners from provincial and municipal working unit, which was more practical and effective when a novel framework forming.…”
Section: Development Of a Flexible Indicator Systemmentioning
confidence: 99%
“…The Analysis Hierarchical Process (AHP), which was formally proposed by Thomas L. Saaty, was adopted for the weights calculation. The method has been proved to be a reliable tool to facilitate systematic and logical decision-making processes, and widely adopted in solving social, industrial and healthy problems via constructing a judgment matrix for analyzing and determining the weights of each criterion [45,56,57]. In this research, the 8 experts who had participated in the Delphi method were invited to further rate the weights of indicators in the AHP survey to ensure the effectiveness and the consistency of the consultation as well as the reliability of the results.…”
Section: Construction and Analysis Of Comprehensive Indexesmentioning
confidence: 99%